Strategi Copywriting Untuk Menulis Promosi Offline Atau Online - Dede Suleman (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
In the marketing era, more effort is needed to attract consumers to read advertisements made by business actors. Therefore marketers must be able to make sentences that can make consumers interested in seeing further advertisements and arrive at the stage of making purchases and many things that will happen later change into more complex challenges that will be faced by entrepreneurs where the presence of new technology is one of the originator of a new consumer lifestyle that makes it easier for them to carry out their living activities in a society that is smarter with the presence of new technology. Strategy acceleration must be carried out especially in the field of marketing and more specifically in digital marketing. This is important because almost all information is circulating on social media and because of that copywriting is a skill that must be owned by business people, especially for those who use the internet as a means of promotion and in this case more specifically on social media. The ultimate goal of this training is to enable business actors to create effective advertisements.